Probing the boundary between star clusters and dwarf galaxies: a MUSE view on the dynamics of Crater/Laevens I - Voggel, Karina; Grebel, Eva K.; Frank, Matthias Johannes (Arxiv, 2016)
We present MUSE observations of the debated ultra faint stellar system Crater. We spectroscopically confirm 26 member stars of this system via radial velocity measurements. We derive the systematic instrumental velocity uncertainty of MUSE spectra to be 2.27$\rm \,km\,s^{-1}$. This new dataset increases the confirmed member stars of Crater by a factor of 3. One out of three bright blue stars and a fainter blue star just above the main-sequence-turn-off are also found to be likely members of the system. The observations reveal that Crater has a systemic radial velocity of $v_{\rm sys}=148.18^{\rm +1.08}_{\rm -1.15}\rm \,km\,s^{-1}$, whereas the most likely velocity dispersion of this system is $σ_{\rm v}=2.04^{\rm +2.19}_{\rm -1.06} \rm \,km\,s^{-1}$. The total dynamical mass of the system, assuming dynamical equilibrium is then $M_{\rm tot}=1.50^{+4.9}_{-1.2}· 10^{\rm 5}M_{\odot}$ implying a mass-to-light ratio of M/L$_{\rm V}$=8.52$^{+28.0}_{-6.5}\, M_{\odot}/L_{\odot}$, which is consistent with a purely baryonic stellar population within its errors and no significant evidence for the presence dark matter was found. We also find evidence for a velocity gradient in the radial velocity distribution. We conclude that our findings strongly support that Crater is a faint intermediate-age outer halo globular cluster and not a dwarf galaxy.
Gesehen am 13.10.2017